Prospects of Using Biological Test-Systems for Evaluation of Effects of Electromagnetic Fields - Marynchenko, Lolita; Nizhelska, Aljona; Shirinyan, Aram; Makara, Volodymyr (Innovative Biosystems and Bioengineering, 2019)
Electromagnetic fields (EMF) can occur both naturally and due to human activity. Nowadays, through the innovative communication technologies, the new sources of artificial EMFs are widely disseminated. Therefore, one needs to study the artificial EMFs and mechanisms of their influence on biosystems. The paper deals with the issues of the influence of artificial EMFs on human health, environment and biological objects. The experimental and theoretical investigations concerning an action of EMF are analyzed. The description of principles of standardization of non-specific EMFs and protection from the influence of man-made fields is presented. Possible mechanisms of EMF and electromagnetic radiation (EMR) action on biological objects, including those due to the accumulation of biogenic magnetic nanoparticles in an organism, are discussed. The aim of the research is to review state-of-the-art methods for detecting the biological effects of non-thermal non-ionizing EMF and EMR and to determine the prospects of using biological test-systems for evaluation of effects of EMFs. Hereby, the main attention is drawn to EMF sensors based on the cultures of microorganisms. The classification of existing test-systems is proposed according to criteria: 1) vitality of cells; 2) motor activity of cells; 3) bioluminescence and color changes under the influence of EMF. The need to develop simple and reliable biological indicators for various types of EMFs, especially for ultrahigh-frequency radiation in connection with the introduction of 5G communications technology, is substantiated. The necessity of standardized test-protocols for comparison of research results is emphasized. It is shown that the description of corresponding experiments should be accompanied by the following features: 1) name of the cell culture; native or modified cells; 2) physical characteristics of EMF or EMR (frequency, power, modulation, source type); 3) exposure duration of; 4) list of parameters to be investigated; 5) research methods; 6) absolute measurements, results and the relative magnitude of an effect; 7) what does the influence depend on (temperature, age of cell culture, composition of the nutrient medium); 8) inheritance of changes in cells; 9) relaxation time of the effect.